2011
DOI: 10.1118/1.3533897
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of patient size‐corrected, scanner‐independent organ dose estimates for abdominal CT exams

Abstract: Purpose:A recent work has demonstrated the feasibility of estimating the dose to individual organs from multidetector CT exams using patient-specific, scanner-independent CTDI vol -to-organ-dose conversion coefficients. However, the previous study only investigated organ dose to a single patient model from a full-body helical CT scan. The purpose of this work was to extend the validity of this dose estimation technique to patients of any size undergoing a common clinical exam. This was done by determining the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
172
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 139 publications
(190 citation statements)
references
References 21 publications
9
172
0
Order By: Relevance
“…Several studies have shown, for the same scanner output (ie, the same CTDI vol ), that smaller patients actually absorb more radiation dose than larger patients (15,16). Therefore, if two patients of different size are scanned with the same technical factors, then the scanner would report an identical CTDI vol value, but the actual absorbed dose would be higher for a smaller patient than a larger patient.…”
Section: Understanding Of Subgroup Radiation Risk Is Recommendedmentioning
confidence: 99%
“…Several studies have shown, for the same scanner output (ie, the same CTDI vol ), that smaller patients actually absorb more radiation dose than larger patients (15,16). Therefore, if two patients of different size are scanned with the same technical factors, then the scanner would report an identical CTDI vol value, but the actual absorbed dose would be higher for a smaller patient than a larger patient.…”
Section: Understanding Of Subgroup Radiation Risk Is Recommendedmentioning
confidence: 99%
“…This approach could be particularly useful in light of the current CT technologies where vendors are varying pitches on the fly throughout an exam or modulating and even switching off the X-ray beam over high risk organs. Further, variants such as the size-specific dose estimate (SSDE) recommended by the American Association of Medical Physicists (AAPM) [6] or even size-specific organ absorbed dose estimates based on the CTDI vol [7] may be useful additions to the dose information displayed on the scanner. An automatically calculated lateral and anteriorposterior dimension (recognising skin edge) for each patient would also assist in size-specific dosimetry.…”
Section: Dosimetry Informationmentioning
confidence: 99%
“…Although the relationship between body habitus and radiation dose in diagnostic CT imaging has been extensively investigated [9][10][11][12][13][14][15][16] , dose estimation in CTF procedures is more compli- Figure 1 Scout CT image of prone phantom demonstrating inner (*) and outer (**) layers of 4.5-cm-thick circumferential adipose-equivalent material. A single layer was applied to simulate average body habitus, and two layers were applied to simulate oversize habitus.…”
Section: Introductionmentioning
confidence: 99%